Hyaluronic acid with or without bone marrow derived-mesenchymal stem cells improves osteoarthritic knee changes in rat model: a preliminary report - Suhaeb, A.M.; Naveen, S.; Mansor, A.; Kamarul, Tunku (2011)
Despite being a complex degenerative joint disease, studies on osteoarthritis (OA) suggest that its progression can be reduced by the use of hyaluronic acid (HA) or mesenchymal stem cells (MSC). The present study thus aims to examine the effects of MSC, HA and the combination of HA-MSC in treating OA in rat model. The histological observations using O'Driscoll score indicate that it is the use of HA and MSC independently and not their combination that delays the progression of OA. In conclusion, the preliminary study suggest that the use of either HA or MSCs effectively reduces OA progression better than their combined use.